Family nurture intervention alters relationships between preterm infant EEG delta brush characteristics and term age EEG power. Issue 8 (August 2020) - Welch, Martha G.; Grieve, Philip G.; Barone, Joseph L.; Ludwig, Robert J.; Stark, Raymond I.; Isler, Joseph R.; Myers, Michael M.
Highlights: Family Nurture Intervention (FNI) in preterm infants alters characteristics of delta brush EEG bursts (DB). EEG bursts at ~35 weeks are correlated with EEG power at term age and are stronger in standard care infants. Effects of FNI on DBs at ~35 weeks do not mediate effects of FNI on term age EEG power or coherence. Abstract: Objective: Family Nurture Intervention (FNI) facilitates mother/infant emotional connection, improves neurodevelopmental outcomes and increases electroencephalogram (EEG) power at term age. Here we explored whether delta brushes (DB), early EEG bursts that shape brain development, are altered by FNI and mediate later effects of FNI on EEG. Methods: We assessed DB characteristics in EEG data from a randomized controlled trial comparing infants with standard care (SC, n = 31) versus SC + FNI (n = 33) at ~35 and ~40 weeks GA. Results: Compared to SC infants, FNI infant DB amplitude increased more from ~35 to ~40 weeks, and FNI infants had longer duration DBs. DB parameters (rate, amplitude, brush frequency) at ~35 weeks were correlated with power at ~40 weeks, but only in SC infants. FNI effects on DB parameters do not mediate FNI effects on EEG power or coherence at term. Conclusions: DBs are related to subsequent brain activity and FNI alters DB parameters. However, FNI's effects on electrocortical activity at term age are not dependent on its earlier effects on DBs. Significance: While early DBs can have important effects on later brain activity in preterm infants, facilitating emotional connection with FNI may allow brain maturation to be less dependent on early bursts.